A DFT study of structural, electronic and optical properties of pristine and intrinsic vacancy defects containing barium zarconate (BaZrO3) using mBJ potential. (23rd December 2020) - Erum, Nazia; Iqbal, Muhammad Azhar; Bashir, Imran
Abstract: First principles calculations, using Full Potential Linearized Augmented Plane Wave (FP-LAPW) method within the framework of density functional theory (DFT), are used to study structural, electronic and optical properties of barium zirconate (BaZrO3 ) in its pristine and intrinsic vacancy defects using the supercell approach. The calculated structural parameters with four semi-local exchange-correlation functionals Local Density Approximation (LDA), Generalized Gradient Approximation (GGA), Perdew–Burke–Ernzerhof for solids (PBEsol) GGA, Wu and Cohen (WC) GGA includes, lattice parameter ao, ground state volume Vo, bulk modulus Bo, total energies Eo, and bond lengths of Ba, Zr and O atoms. Furthermore, to avoid the underestimation of the band profile by other DFT schemes we highlight the LDA plus modified Becke–Johnson (mBJ) potential in lieu of attaining opto-electronic aspects close to the anticipated experimental findings. The computed electronic band gap shows that band profile remains indirect with small difference in detail. The optical properties of Ba, Zr and O vacancy containing 2 × 2 × 2 supercells of BaZrO3 are calculated using real and imaginary part of dielectric function. The real part of the dielectric function using mBJ_s modification reveals that static dielectric constant of BaZrO3 is 3.8 that is, in excellent agreement with the experimental value of 4.0. The structural, electronic and optical properties of pristine BaZrO3 along with its non-stoichiometric intrinsic vacancy containing forms are studied to provide experimentalist with a better understanding of its physical properties which are vital for its functional utilization.